Cultivating Future Leaders: Faculty Leadership Seminar at Clermont College - Kim Jacobs-Beck (Academic Chairpersons Conference Proceedings, 2015)
Like many universities, ours faced the challenge of needing to cultivate future department chairs and other academic leaders. Current department chairs developed a leadership seminar, a year-long series of workshops and roundtables discussions for faculty from every department. The seminar alternates with a broader-based, informal leadership discussion series.
Keywords: Faculty development; leadership; administration; training; chairpersons